PENGARUH KUALITAS PELAYANAN, HARGA DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL DAFAM SEMARANG - Zunta Ovidani; Wahyu Hidayat (Universitas Diponegoro, 2020)
Hospitality is one of the organizations engaged in lodging services. Dafam Semarang hotel is one of the service businesses located in the city of Semarang. This hotel, which has been around for 10 years, has advantages and disadvantages, which in turn results in a decrease in income caused by several factors. This research has the aim to determine the effect of service quality, price and trust on customer satisfaction. This research used explanatory research. The sample were taken as many as 100 respondents with criteria are using Dafam Semarang hotel services, have a minimum age of 25 years and have used the services of Dafam Semarang hotel room at least 2 times. The process of collecting data are using questionnaire instruments, follow-up interviews and observations. The analytical tool used is SPSS 21.0 for Windows with validity test, reliability test, correlation coefficient test, determination coefficient, simple and multiple regression analysis, and significance test (t test and F test). The results showed that simultaneously, service quality variables (X1) price (X2) and trust (X3) together had a positive effect on customer satisfaction variables (Y). From the results of the coefficient of determination, the variable service quality is 0.101 or 10.1%, the price variable is 0.413 or 41.3%, the trust variable is 0.62 or 6.2%, which when added up does not reach 100%. Based on these results, it can be concluded that the majority of customer satisfaction at Dafam Hotel are service quality, price, and trustworthiness, while the remainder is a contribution made by other variables outside this study.